2020
DOI: 10.1002/alz.12150
|View full text |Cite
|
Sign up to set email alerts
|

Small vessel disease more than Alzheimer's disease determines diffusion MRI alterations in memory clinic patients

Abstract: * Data used in preparation of this article were obtained from the Dominantly Inherited Alzheimer Network (DIAN) database, the DZNE-Longitudinal Cognitive Impairment and Dementia Study (DELCODE) database, and the Alzheimer's Disease Neuroimaging Initiative (ADNI) database (adni.loni.usc.edu). As such, the investigators within DIAN, DELCODE, and ADNI contributed to the design and implementation of the respective studies and/or provided data but did not participate in analysis or writing of this report. A complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 49 publications
6
43
0
Order By: Relevance
“…Notably, after adjusting for WMH, our results show that the FBA results remained mostly unchanged in both ZJU and ADNI datasets, but the significance level somehow lowered. Our results suggested that WMH did contribute to part of the microstructural alterations in AD patients, which is in accordance with previous results [ 22 ]. Thus, it is necessary to take CSVD burden into account in future AD studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notably, after adjusting for WMH, our results show that the FBA results remained mostly unchanged in both ZJU and ADNI datasets, but the significance level somehow lowered. Our results suggested that WMH did contribute to part of the microstructural alterations in AD patients, which is in accordance with previous results [ 22 ]. Thus, it is necessary to take CSVD burden into account in future AD studies.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, AD is a multifactorial disease with multiple contributors to its pathophysiology, including cerebral small vascular disease (CSVD) [ 21 ]. Recent work suggested that the effects of CSVD on WM integrity should also be accounted for [ 22 ]. After adjusting for WMH, we repeated the same analyses in both ZJU and ADNI datasets and the results we yielded remained mostly unchanged despite of a lower but statistically sound significance level ( Supplementary Material 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In DIAN the other bundle where Aβ and white matter measures were related was the anterior cingulum, another bundle connecting key regions where Aβ accumulates. In line with these results similar associations have been found in DIAN using CSF Aβ (Finsterwalder et al, 2020). On the other hand, in PREVENT-AD, the strongest associations with Aβ were detected in the uncinate fasciculus.…”
Section: Discussionsupporting
confidence: 89%
“…13,36 PSMD, like other DTI metrics, appears to be more sensitive to cSVD-related white matter abnormalities than to neurodegenerative pathology. 13,42 The low burden of cSVD pathology observed in our non-CAA sample might explain the absence of association between PSMD and processing speed.…”
Section: Discussionmentioning
confidence: 88%